Gradient foaming of polycarbonate/carbon nanotube based nanocomposites with supercritical carbon dioxide and their EMI shielding performances. (24th February 2015) - Monnereau, Laure; Urbanczyk, Laetitia; Thomassin, Jean-Michel; Pardoen, Thomas; Bailly, Christian; Huynen, Isabelle; Jérôme, Christine; Detrembleur, Christophe
Abstract: Sorption and diffusion of supercritical carbon dioxide ( sc CO2 ) into polycarbonate (PC) nanocomposites loaded with 0, 1 and 2 wt% of multi-walled carbon nanotubes (MWNTs) have been investigated. After determination of the saturation equilibrium, the samples have been saturated with sc CO2 to ensure a partial foaming with a density gradient from the surface to the center of the samples and the morphology of the porous materials has been analyzed by SEM. The gradient materials were very advantageous for EMI shielding since the foamed structure at the surface had low dielectric constant and limited the reflection of the EM signal while the presence of highly conductive solid in the middle ensured a high absorption of the electromagnetic radiation. Graphical abstract: Highlights: Preparation of polycarbonate/carbon nanotube foams exhibiting a gradient morphology. Gradient foaming by the supercritical carbon dioxide technology. The gradient nanocomposite foams are excellent EMI absorbers.